Information System for South Aceh Historical Stories - Sukma Achriadi; M. Arinal Ihsan (Jurnal Inotera, 2023)
Making this application aims to create an application that can accommodate historical stories in South Aceh in the form of a reading application that is easily accessible. The making of this application is made with a programming language that is processed into an application that contains historical stories obtained from various sources as well as from narrators or historical storybooks in South Aceh. From the development of this application, a lot of knowledge was gained from historical stories in South Aceh. Making this application produces an application that includes useful and historical stories so that all historical stories in South Aceh are not lost and forgotten and can also be accessed easily by anyone.